PEMANFAATAN GETAH Excoecaria agallocha SEBAGAI BAHAN AKTIF PEMBASMI HAMA TRISIPAN (Cerithidea sp.) - Setyastuti, Tri Ari; Puspitasari, Indah; Sukamto, Dwi; Asmarany, Anja (Chanos Chanos, 2022)
Chemicals as pest and disease control in aquaculture production are suspected to contain potential toxicity to human health as well as harm to the environment, so this study aimed to use mangrove plants as pesticides made of organic material for pest control in shrimp ponds. One of the pests that are very disturbing is trisipan (Telescopium telescopium) from the Mollusca group. This study aimed to identify the active compounds contained in the latex of Excoecaria agallocha, to determine the cytotoxicity activity of the latex of Excoecaria agallocha and to determine the LC50 of the latex of E. agallocha against Trisipan. This research was conducted from September to December 2019 at the Mangrove Center Pulokerto Pasuruan and the Fish Pathology Laboratory of the Marine and Fisheries Polytechnic of Sidoarjo. The method used is experimental 6 treatments with 3 replications.The results that can be concluded from this study are that the active compound content of Excoecaria agallocha latex has not been determined because it is still in the testing process, the cytotoxicity activity of Excoecaria agallocha sap in brackish water media is higher than the cytotoxicity activity in freshwater media and LC50 of resin E. agallocha against Trisipan was shown in Trisipan with brackish water media and a dose of 400 ppm.